Glycolysis Rate-Limiting Enzymes: Novel Potential Regulators of Rheumatoid Arthritis Pathogenesis - Zuo, Jianlin; Tang, Jinshuo; Lu, Meng; Zhou, Zhongsheng; Li, Yang; Tian, Hao; Liu, Enbo; Gao, Baoying; Liu, Te; Shao, Pu (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a classic autoimmune disease characterized by uncontrolled synovial proliferation, pannus formation, cartilage injury, and bone destruction. The specific pathogenesis of RA, a chronic inflammatory disease, remains unclear. However, both key glycolysis rate-limiting enzymes, hexokinase-II (HK-II), phosphofructokinase-1 (PFK-1), and pyruvate kinase M2 (PKM2), as well as indirect rate-limiting enzymes, 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (PFKFB3), are thought to participate in the pathogenesis of RA. In here, we review the latest literature on the pathogenesis of RA, introduce the pathophysiological characteristics of HK-II, PFK-1/PFKFB3, and PKM2 and their expression characteristics in this autoimmune disease, and systematically assess the association between the glycolytic rate-limiting enzymes and RA from a molecular level. Moreover, we highlight HK-II, PFK-1/PFKFB3, and PKM2 as potential targets for the clinical treatment of RA. There is great potential to develop new anti-rheumatic therapies through safe inhibition or overexpression of glycolysis rate-limiting enzymes.